2016
DOI: 10.1037/a0039902
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal examination of perceived discrimination and depressive symptoms in ethnic minority youth: The roles of attributional style, positive ethnic/racial affect, and emotional reactivity.

Abstract: Although perceived ethnic/racial discrimination is well established as a risk factor for depressive symptoms in ethnic minority youth, few studies have examined their longitudinal relationship over time. This study examined whether a negative attributional style, positive ethnic/racial affect, and emotional reactivity moderated the longitudinal relationship of perceived peer or adult discrimination and depressive symptoms in a sample of African American and Latino high school students (n = 155). African Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 58 publications
2
23
0
Order By: Relevance
“…All studies that examined discrimination found significant relationships between discrimination and depressive symptoms. Societal discrimination (Behnke et al, 2011), anticipated discrimination (Paat, 2016), discrimination stress (Cervantes et al, 2012; Cervantes et al, 2015), perceived discrimination (Basáñez et al, 2013; Chithambo et al, 2014; Gonzales-Backen et al, 2017; Lorenzo-Blanco et al, 2011; Potochnick, Perreira, & Fuligni, 2012; Potochnick & Perreira, 2010; Young, 2016), ethnic discrimination from teachers and peers (Huq et al, 2016; Stein, Supple, Huq, Dunbar, & Prinstein, 2016), and ethnic microaggression frequency (Huynh, 2012) all had significant positive associations with depressive symptoms in Latino/a adolescents. These studies thus provide strong evidence for a significant relationship between discrimination and depressive symptoms in Latino/a adolescents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies that examined discrimination found significant relationships between discrimination and depressive symptoms. Societal discrimination (Behnke et al, 2011), anticipated discrimination (Paat, 2016), discrimination stress (Cervantes et al, 2012; Cervantes et al, 2015), perceived discrimination (Basáñez et al, 2013; Chithambo et al, 2014; Gonzales-Backen et al, 2017; Lorenzo-Blanco et al, 2011; Potochnick, Perreira, & Fuligni, 2012; Potochnick & Perreira, 2010; Young, 2016), ethnic discrimination from teachers and peers (Huq et al, 2016; Stein, Supple, Huq, Dunbar, & Prinstein, 2016), and ethnic microaggression frequency (Huynh, 2012) all had significant positive associations with depressive symptoms in Latino/a adolescents. These studies thus provide strong evidence for a significant relationship between discrimination and depressive symptoms in Latino/a adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…BSS = Bicultural Stress Scale (Romero & Roberts, 2003); CDI-2 = Children's Depression Inventory-2 (Kovacs & Multi-Health Systems Staff, 2011); HSI-AV = Hispanic Stress Inventory-Adolescent Version (Cervantes, Fisher, Córdova, & Napper, 2012); LA = Los Angeles; MFQ = Mood and Feelings Questionnaire (Angold et al, 1987); NC = North Carolina. 2016), ethnic discrimination from teachers and peers (Huq et al, 2016;Stein, Supple, Huq, Dunbar, & Prinstein, 2016), and ethnic microaggression frequency (Huynh, 2012) all had significant positive associations with depressive symptoms in Latino/a adolescents. These studies thus provide strong evidence for a significant relationship between discrimination and depressive symptoms in Latino/a adolescents.…”
Section: Ces-dmentioning
confidence: 94%
“…Other studies found no changes across 10th to 12th grades (Sirin et al 2015; no information on country of origin), or different classes of trajectories across 9th grade to three years post high school (i.e., increasing, decreasing, and two stable; Unger et al 2014; no information on country of origin)). Regardless of mean level trajectories, there has been significant individual variability in trajectories such that greater levels of discrimination across time have been associated with worse depressive (Stein et al 2016;19% Latinx) and/or anxiety (Sirin et al 2015) symptoms in multiethnic samples. However, no past study has examined how peer discrimination longitudinally relates to depressive and/or anxiety symptoms in a solely Latinx sample.…”
Section: Longitudinal Studies Of Peer Discriminationmentioning
confidence: 99%
“…Ethnic discrimination can be conceptualized as being treated unfairly or negatively, such as being excluded or harassed verbally, because of one's ethnic background (Garrett et al, 2017;Jasinskaja-Lahti et al, 2003). The negative effects of discrimination on the well-being of adolescents of immigrant descent 1 are well documented (e. g., Maes et al, 2014;Reitz et al, 2015;Stein et al, 2015).…”
mentioning
confidence: 99%
“…Notably, only 4 % were conducted in Europe. However, experiencing ethnic discrimination is a part of everyday life among adolescents of immigrant descent in Germany and the rest of Europe (Berry et al, 2006;Frankenberg et al, 2013), and it poses adjustment threats socioemotionally (e. g., poor mental health), relationally and academically (e. g., negative behavior and poor academic achievement) (see Aichberger et al, 2015;Stein et al, 2015). Germany, with its long-standing history of immigration, in recent years has continued to record among the highest arrivals of immigrants and asylum-seekers in continental Europe (Bundesamt für Migration und Flüchtlinge, 2018).…”
mentioning
confidence: 99%